The Origin of Abandon and Random - Diensberg, Bernhard (Studia Anglica Posnaniensia, 2011)
Modern English ban and related lexemes will be shown to have their origin in common with abandon, the latter of disputed etymology. This applies to a still greater extent to random, for the origin of which a plausible solution will be presented. A last paragraph is devoted to the etymology of Modern English PLAN.